Effect of moisture levels on the survival of Trichoderma harzianum in soil - R. RAMABADRAN, J. JAYARAJ and (Indian Phytopathology, 2002)
Moisture levels of 10% were shown to be the best conditions for the efficient growth and multiplication of T. harzianum in clay loam soil in Tamil Nadu, India.